2010
DOI: 10.1093/jac/dkq415
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O25b-ST131: a pandemic, multiresistant, community-associated strain

Abstract: Escherichia coli sequence type 131 (ST131) is a worldwide pandemic clone, causing predominantly community-onset antimicrobial-resistant infection. Its pandemic spread was identified in 2008 by utilizing multilocus sequence typing (MLST) of CTX-M-15 extended-spectrum β-lactamase-producing E. coli from three continents. Subsequent research has confirmed the worldwide prevalence of ST131 harbouring a broad range of virulence and resistance genes on a transferable plasmid. A high prevalence of the clone (∼30%-60%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
556
7
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 633 publications
(601 citation statements)
references
References 100 publications
31
556
7
7
Order By: Relevance
“…This increase in resistance among E coli in the community has been reported in numerous studies 3,4,[39][40][41] and may be due to several factors, including increasing reliance on outpatient medical management, increasing antimicrobial use in the outpatient setting, transmission of drug-resistant strains from the hospital into the community, or expansion of drug-resistant clones within the community. 3,14,18,42 Because resistance to fluoroquinolone and fluoroquinolone plus trimethoprim-sulfamethoxazole increased more markedly than resistance to other antibiotics among our E coli isolates from 2005 through 2009, we hypothesize that there has been expansion of drug-resistant clones within Olmsted County. In the United States, more than half of E coli with resistance to fluoroquinolones or fluoroquinolones plus trimethoprim-sulfamethoxazole are sequence type 131, 1 a highly drug-resistant and globally disseminated clonal group first reported in 2008.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This increase in resistance among E coli in the community has been reported in numerous studies 3,4,[39][40][41] and may be due to several factors, including increasing reliance on outpatient medical management, increasing antimicrobial use in the outpatient setting, transmission of drug-resistant strains from the hospital into the community, or expansion of drug-resistant clones within the community. 3,14,18,42 Because resistance to fluoroquinolone and fluoroquinolone plus trimethoprim-sulfamethoxazole increased more markedly than resistance to other antibiotics among our E coli isolates from 2005 through 2009, we hypothesize that there has been expansion of drug-resistant clones within Olmsted County. In the United States, more than half of E coli with resistance to fluoroquinolones or fluoroquinolones plus trimethoprim-sulfamethoxazole are sequence type 131, 1 a highly drug-resistant and globally disseminated clonal group first reported in 2008.…”
Section: Discussionmentioning
confidence: 66%
“…In the United States, more than half of E coli with resistance to fluoroquinolones or fluoroquinolones plus trimethoprim-sulfamethoxazole are sequence type 131, 1 a highly drug-resistant and globally disseminated clonal group first reported in 2008. 2,3,5,17 We are currently performing molecular epidemiology studies to determine whether clonal expansion of sequence type 131 or other clonal groups has contributed to the rapid increase in drug resistance we observed.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The global spread of the E. coli sequence type (ST131) with multiple antimicrobial resistance genes and the horizontal transfer gene are of great concern in the development of resistance to prophylactic antibiotics. 22 Patient-specific risk factors for FQ resistance include increasing age, comorbidities, international travel, recent hospitalization, prior FQ exposure and urinary catheterization. 1,3,23,24 The aim of our study was to characterize the prescribing patterns of prophylactic antibiotics prior to TRUS-PB in a large urban centre.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent analysis using MLST showed that strains A-E all belonged to an extremely successful clone of E. coli of ST131 which is now known to have disseminated globally [62,63]. It is also of note that E. coli ST131 is commonly resistant to quinolones and was a likely contributor to the increase in ciprofloxacin resistance seen in E. coli during the 2000s [63]. Hence the increase in resistance to ciprofloxacin and third-generation cephalosporins in E. coli during this time is probably explained in large part by clonal expansion following the emergence of ST131 in the UK.…”
Section: (I) Enhanced Surveillance Of Methicillin-resistant Staphylocmentioning
confidence: 99%